2011
DOI: 10.1007/s13277-011-0268-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous activity distribution of 177Lu-DOTA0-Tyr3-octreotate and effects on somatostatin receptor expression in human carcinoid GOT1 tumors in nude mice

Abstract: The aim of this study was to investigate the activity distribution in neouroendocrine tumors after diagnostic, or therapeutic, amounts of [(177)Lu-DOTA(0)-Tyr(3)]-octreotate and to investigate how the activity distribution influences the absorbed dose. Furthermore, the activity distribution of a second administration of radiolabeled octreotate was studied. Nude mice with subcutaneously grown human midgut carcinoid (GOT1) were injected intravenously with different amounts of (177)Lu-octreotate. At different tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
2
7
1
Order By: Relevance
“…These findings are not in accordance with previous results, which did not show any increased 177 Lu-octreotate uptake in normal tissues [12]. An additional explanation to the higher activity concentrations found in tumoral and non-tumoral SSTR-expressing tissues might be that the priming administration influences vascular perfusion.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…These findings are not in accordance with previous results, which did not show any increased 177 Lu-octreotate uptake in normal tissues [12]. An additional explanation to the higher activity concentrations found in tumoral and non-tumoral SSTR-expressing tissues might be that the priming administration influences vascular perfusion.…”
Section: Discussioncontrasting
confidence: 97%
“…The kinetics of SSTR expression are clearly time dependent, and further studies are needed to clarify the mechanisms by which priming improves the uptake of 177 Lu-octreotate in tumor tissue, as well as the dose-response relation between administered activity and SSTR expression. We have previously reported an increased tumor uptake of 111 In-octreotide following 7.5 MBq 177 Lu-octreotate in GOT1 xenografts, but not following 30 MBq 177 Lu-octreotate [12, 13]. Thus, the 15 MBq single administration may be too high to result in detectable SSTR up-regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, due to impaired delivery to central tumor or reduced radiosensitivity due to hypoxic conditions [47] . The latter explanation is in agreement with a previous study of the GOT1 tumor model, where higher proliferation was found in peripheral tumor parts, although there was a higher uptake of 177 Lu-octreotate in central tumor parts [48] .The proliferation would facilitate apoptosis induced by DNA damage, and the central uptake of 177 Lu-octreotate indicates adequate delivery and that the lower response must be caused by something else, such as hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…wild type GOT1 Tumor Cells in vitro Antitumoral effects of the somatostatin analogs octreotide and lanreotide in patients with NETs have been proven in clinical phase III studies [64][65][66][67] [70][71][72][73] . Therefore, we aimed to investigate the effects of octreotide in GOT1 cells in vitro alone and in combination with NVP-CGM097.…”
Section: Octreotide Does Not Affect the Proliferation Of P53mentioning
confidence: 99%